If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3b + 23 = 80 Reorder the terms: 23 + -3b = 80 Solving 23 + -3b = 80 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -3b = 80 + -23 Combine like terms: 23 + -23 = 0 0 + -3b = 80 + -23 -3b = 80 + -23 Combine like terms: 80 + -23 = 57 -3b = 57 Divide each side by '-3'. b = -19 Simplifying b = -19
| 90=60t | | 2(k-4)=5k+2 | | x-4x-3=0 | | 2(k-4)=5k-2 | | 17x+7x=14-36 | | -4x-1+6x+4= | | 8(r-5)(r+5)=0 | | -4x+2+7x+3= | | 9x+4x-8x=8+7 | | 2(x-3)=(2x+5) | | 6y+2(3+6.5y)=2.5+15.5y | | 3+1b=5 | | 11p-9+8p-7+14=12p+9p+4 | | 8x-24y=144 | | 0.5r+5.2=2.8 | | 7(24-x)=5x | | 4x^2-2ax-2bx+ab=0 | | 12-k=22 | | 4x-16y=144 | | 0.4y+8=-2 | | 5[-3(4x+5)+3(5x-4)]= | | -14+11p-10p-6= | | -18+12f+16f+15= | | -5x-3y=16 | | (6)*(-7)= | | 18c+4c+7-9= | | -14-(-1.5)= | | -6+2x-3-10x= | | -22-22= | | b^4+12b^2p^2+36p^4= | | 21+(-19)+(-24)= | | -7x^2-13x+2=0 |